Third world tomorrow: a report from the battlefront in the war against poverty - Harrison, Paul (London, 1983)
This book is intended as a survey of the new approaches in each major field, a field report on the war against poverty for the Third Development Decade. It is illustrated by those projects which I have visited in the course of six years' research and travel in thirteen countries between 1974 and 1980: India (three visits, July/August 1974, March 1976 and June 1978), Sri Lanka (April/May 1975), Upper Volta and Ivory Coast (February/March 1976), Colombia and Peru (Nove ber/December 1976), Brazil (May 1977), Indonesia and Singapore (September/October 1977), Bangladesh (September 1978), Costa Rica and Cuba (November/December 1979) and Kenya (May 1980). My aim has been to provide a wide-ranging survey for the general reader interested in current affairs, as well as for young and old students of development and specialists in particular fields who may be interested to find out a little about what is happening in other fields. The wide scope has forced me to be selective rather than exhaustive.
Keywords: Poverty